Customer Satisfaction of Logistics Providers’ Services - Wan Ahmad, Wan Nurul Karimah; Shamsuddin, Alina; Tham, Jia Hui (Research in Management of Technology and Business, 2021)
Logistics companies provide logistics and warehousing services to satisfy customer requirements. However, studies related to customer satisfaction of logistics providers’ services in Malaysia are lacking. The purpose of this research is therefore to identify the level of customer satisfaction of the logistics services. It focuses on identifying customers’ service expectations and service performance of courier service companies that will affect the customer satisfaction. An online survey was used to collect data to achieve the purpose of this research. A descriptive analysis was conducted to analyze the level of customers’ service expectations and logistics providers’ service performance. The results of mean importance (expectation) and mean performance (satisfaction) were 4.295 and 3.975 respectively. The overall Service Quality Gap (SQG) among service providers in Malaysia was at a low level of service performance (-0.337). Customers had high expectations towards providers’ services, but the performance cannot satisfy their needs. According to the Consumer Satisfaction Index (CSI) score, which was used to evaluate the level of customer satisfaction, they were highly satisfied with the strong tracking system provided by logistics companies (4.210). The providers could improve their services continuously to solve the performance gap between customers’ expectations with perceived experience.